2002
DOI: 10.1002/bem.10004
|View full text |Cite
|
Sign up to set email alerts
|

Brief exposure to a 50 Hz, 100 μT magnetic field: Effects on reaction time, accuracy, and recognition memory

Abstract: The present study investigated both the direct and delayed effects of a 50 Hz, 100 microT magnetic field on human performance. Eighty subjects completed a visual duration discrimination task, half being exposed to the field and the other half sham exposed. The delayed effects of this field were also examined in a recognition memory task that followed immediately upon completion of the discrimination task, Unlike our earlier studies, we were unable to find any effects of the field on reaction time and accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 19 publications
(17 reference statements)
0
29
2
Order By: Relevance
“…Kazantzis et al [1998] showed, on the same task, a small statistical improvement in accuracy, but relaxed the alpha level from the conventional P ¼.05 to P ¼.30. These results, however, were not reproduced by Podd et al [2002].…”
Section: Introductioncontrasting
confidence: 77%
“…Kazantzis et al [1998] showed, on the same task, a small statistical improvement in accuracy, but relaxed the alpha level from the conventional P ¼.05 to P ¼.30. These results, however, were not reproduced by Podd et al [2002].…”
Section: Introductioncontrasting
confidence: 77%
“…Others have failed to find any effects [Kurokawa et al, 2003;Delhez et al, 2004]. Most of these studies, with the exception of Podd et al [2002], do not investigate effects over a longer post-exposure duration. An overview of the results of these studies can be found in Table 3.…”
Section: Studies Involving Performance Measures: Time Course Of Effectsmentioning
confidence: 85%
“…Effects have been noted immediately during the exposure period [Shupak et al, 2004a], and following a delay [Podd et al, 2002]. Others have failed to find any effects [Kurokawa et al, 2003;Delhez et al, 2004].…”
Section: Studies Involving Performance Measures: Time Course Of Effectsmentioning
confidence: 93%
See 1 more Smart Citation
“…Some few researchers have focused on MF effects on electrical activity of brain, where the cognitive and perceptual effects of MF exposure were explored [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%